Water Fights Back in Lagos: A Performance Reading of Aqua-Terrestrial Futures in Ojo Bakare’s “Ekun Omi” - Princewill Chukwuma Abakporo; Abdulmalik Adakole Amali; Fidelis Enang Egbe; Stanley Timeyin Ohenhen (eTropic: electronic journal of studies in the tropics)
The Nigerian tropics is home to diverse ecosystems and rich cultural traditions. Taking up water as a material and symbolic force in relation to urbanisation, ecological deterioration, and colonial history, this work analyses Ojo Bakare's play “Ekun Omi” [When Water Cries] in a performative reading of Lagos' aqua-terrestrial futures. Through metaphor, the African theatre production examines the complex interaction between the city's aquatic systems and its human residents in light of flooding, climate change, overpopulation, and the socio-political marginalisation of Indigenous knowledge. Drawing on ecocriticism and the blue humanities, this paper takes a multifaceted approach to understanding water as a victim and agent of ecological retribution. It highlights the transformative power of Bakare’s work in depicting the ecological crisis in Lagos, while engaging the audience in collective responsibility for the future. “Ekun Omi” provides a critical and speculative analysis of Lagos' trajectory, showcasing how any viable future for the city must acknowledge the intricate bond between humans and the natural world—especially watery domains.